A Study of Relationship Between Asthma Control Test, Lung Function, & Hospitalization - Putra, M Yusuf Adira; Tarigan, Amira Permatasari; Pradana, Andika; Resti, Riska; Ramadhani, Adini Arifah; Nasution, Syafiah Amalina (CoinReads Media Prima, 2024)
Introduction: The Asthma Control Test (ACT), developed in 2004, is a crucial tool for assessing asthma control. It facilitates discussions between patients and healthcare providers, guiding treatment decisions based on symptom severity. ACT evaluates symptoms over the past four weeks, while pulmonary function tests like forced expiratory volume in one second (FEV1) and peak expiratory flow (PEF) provide objective measures of airway function, offering complementary insights. Method: This cross-sectional study was conducted at Prof. Chairuddin Panusunan Lubis USU Hospital. Asthma patients were recruited, their characteristics documented through interviews, and spirometry was performed to assess lung function. Results: A significant proportion of patients had uncontrolled asthma based on ACT scores, which correlated with decreased lung function and higher risks of exacerbations. The study also explored characteristics of lung adenocarcinoma patients. Most were male (76.4%), heavy smokers (70.6%), and aged over 60 (52.9%). A majority (70.6%) were at Stage IVA, with pleural metastases being the most common. ALK mutations were detected in 5.8% of cases using immunohistochemistry. Conclusion: Achieving optimal asthma control remains a priority to reduce exacerbation risks and improve outcomes. ACT is a practical, patient-centered tool for identifying uncontrolled asthma and guiding management strategies. The adenocarcinoma findings highlight the need for early detection and targeted therapies in lung cancer care. These results reinforce the value of combining patient-reported outcomes and objective tests in disease management.